KANDUNGAN LOGAM Fe DAN Pb TOTAL DALAM AIR DAN SEDIMEN DI KAWASAN PELABUHAN PADANG BAI SERTA BIOAVAILABILITASNYA - Suprihatin, I. E.; Limbong, P. B.; Ariati, N. K. (Jurnal Kimia (Journal of Chemistry), 2022)
Padang Bai Harbour is a port that serves shipping from Bali to Lombok and vice versa. The port is potentially contaminated with heavy metals due to the shipping activities. Total metal concentrations in seawater and sediments do not provide accurate information about the level of pollution. Bioavailability of the metals is needed to indicate the toxicity.This study aims to determine the total heavy metal content of Fe and Pb in seawater and sediments and their bioavailability in sediments of Padang Bai Harbour. Water samples were prepared by heating at 140ºC for 45 minutes, while sediment samples were wet-digested using a mixture of HNO 3 and HCl (3:1) in an ultrasonic bath at 60ºC for 45 minutes followed by heating at 140ºC for 45 minutes. Speciation was conducted by four stages sequential extraction method. The concentration of Fe and Pb were analyzed by calibration curve using Atomic Absorption Spectrophotometry. The results showed that the total metal concentrations of Fe and Pb in water were 0.12-0.18 mg/L and 0.02-0.21 mg/L, respectively, while in the sediments were 8314.68-27787.05 mg/kg and 20.34-31.44mg/kg, respectively. The speciation obtained the highest bioavailable of Fe and Pb were 0.03% and 8.82%. The highest potentially bioavailable of Fe and Pb were 49.11% and 66.70%, while the highest non-bioavailable Fe and Pb were 67.47% and 41.02%. Based on these results, it can be concluded that the water and sediments in the Padang Bai Harbour area have been polluted by Pb metal because they have exceeded the maximum allowed concentrations. Keywords : bioavailability, Fe, Pb, speciation